UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN GEOGRAFI DENGAN MEDIA PEMBELAJARAN BERBASIS VIDEO DI SMAN 2 KOTA BENGKULU - Citra, Fevi Wira; Venola, Ria; Guntar, Dedi (Universitas Nusa Cendana, 2024)
The research was motivated because one of the X classes at SMAN 2 Bengkulu City, students are less active in participating in learning activities and is a class with a category of students who have problems in learning. it is known that the final assessment of semester 1 of the 2023/2024 school year in class X.8 geography subjects became the class with the lowest score in all X classes. The delivery of learning materials in the classroom still uses conventional methods, namely lecture and discussion methods, causing students to be less active and less interested in participating in geography learning activities. The purpose of the study was to improve the learning outcomes of students in class X.8 in geography subjects. Efforts made to improve student learning outcomes in geography subjects in class X.8 by using one of the learning media, namely video-based media. Video media is expected to attract students' attention, so that students are active in learning and more easily understand the material taught through visuals and audio displayed in video media. The method used in this research is class action research (PTK). Classroom action research was conducted in class X.8 with a total of 39 students. The classroom action research (PTK) was conducted in two cycles. Each cycle consisted of planning stage, implementation stage, observation stage and reflection stage. The instruments used in this study are tests made by researchers in the form of post-test questions and observation sheets consisting of teaching activities of researchers and student activities and documentation. The findings obtained from this study by using video learning media students' activities and learning outcomes in geography class X.8 increased. In cycle I the class average reached 73 and students who reached the KKM 53.12%. In cycle II the class average reached 82.4 and students who reached the KKM 82.85%. So it can be said that in video-based learning activities there is an increase in learning outcomes from cycle I to cycle II reaching 29.6% in class X.8 SMAN 2 Bengkulu City.